2004
DOI: 10.17660/actahortic.2004.636.38
|View full text |Cite
|
Sign up to set email alerts
|

Primary and Secondary Attractants of Flowers in Pear Pyrus Betulifolia

Abstract: The insect attraction of Pyrus betulifolia, a drought-resistant pear species was studied in a Hungarian pear collection between 1998-2002. A detailed floral morphological description was made, including size, shape and colour of flower (secondary attractants). Flowers were homogamous, since both stigma receptivity and anther dehiscence began at the balloon stage, and continued synchronously afterwards. Dynamics of nectar and pollen production (primary attractants) were studied hourly. Nectar secretion could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…These values were higher than those reported in Prunus cerasus and P. avium (0.41-0.57) and lower than in Prunus armeniaca and P. domestica (0.9-3.3 µm), P. avium (1.5-6.0 µm), Prunus laurocerasus (1.21-1.30 µm), and Pyrus sp. (1.26-2.58 µm) [20,21,60,78,79]. In the present study, the evenly distributed cuticle comprised lamellar and reticulate layers and cellulose microfibrils.…”
Section: Nectary Ultrastructurementioning
confidence: 53%
See 3 more Smart Citations
“…These values were higher than those reported in Prunus cerasus and P. avium (0.41-0.57) and lower than in Prunus armeniaca and P. domestica (0.9-3.3 µm), P. avium (1.5-6.0 µm), Prunus laurocerasus (1.21-1.30 µm), and Pyrus sp. (1.26-2.58 µm) [20,21,60,78,79]. In the present study, the evenly distributed cuticle comprised lamellar and reticulate layers and cellulose microfibrils.…”
Section: Nectary Ultrastructurementioning
confidence: 53%
“…In turn, nectary cells in several species of the genus Malus formed from 14 to 31 layers and the gland was from 203 to 430 µm thick [25]. The nectaries of Cydonia oblonga, Cotoneaster betulifolia, and Pyrus betulifolia were composed of 8-15, 3-4, and 3-8 layers, respectively [21,27]. The subnectary parenchyma in the raspberry cultivars analyzed in the presented study was composed of 5-8 layers and its thickness was in the range of 145-199 µm.…”
Section: Nectary Anatomymentioning
confidence: 99%
See 2 more Smart Citations
“…Pollen grains viability test with 1% aceto-orcein shows that all the investigated taxa produced more than 90% viable pollens under in situ condition that ultimately lead to successful participation in pollination mechanism and seed production. Farkas and Orosz-Kovacs (2004) conducted an experiment on pollen grain viability in pear (Pyrus betulifolia) and obtained above 50% viable pollen grains. He concluded that this percentage is sufficient for successful pollination and enough to attract bees.…”
Section: Discussionmentioning
confidence: 99%